Analisis mutu Ikan Tuna selama lepas tangkap - Indah Widiastuti; Sumpeno Putro (UNIVERSITAS SRIWIJAYA, 2010)
Indonesia is one of the leading tuna exporters in the world. The total export volume of tuna in 2004 was 94,221 tons valued at US 243,937 million However, export of fresh tuna has been hampered by several quality problems, particularly high content of histamine and heavy metals. FDA (Food and Drug Administration) reported that during period of 2001-2005, there were 350 cases of tuna rejections in the US due to the above mentioned problem. Likewise, in recent years, exports of tuna from Indonesia to European Union member countries have been subjected to RASFF (Rapid Alert System for Food and Feed) and export suspension by the European Commission. It is obvious therefore, that efforts to improve post harvest handling are highly imperative. This research was conducted in Pelabuhan Ratu, West Java and Research Center For Marine and Fisheries Product Processing and Biotechnology, Jakarta. Newly caught tuna were unloaded and transported to Jakarta with proper icing. Quality changes were monitored, including core temperature of fish, pH, K-value (inosine, hipoxantine, IMP, AMP, ADP, ATP), histamine, heavy metal (Hg and Cd), and microbiology. The pH value of fresh tuna samples upon arrival at the laboratory varied between 5.85-6.01. Whereas the K-value and histamine contents were 2.01- 13.74% and 1.28-1.61 mg/100g respectively. Total microbial count and histamine producing bacteria were 102-2.5 x 104 cfu/g and 101-1.99 x 102 cfu/g respectively. Mercury and cadmium content were 0.076-0.501 ppb and 0.052-0.398 ppb respectively. Â Keywords : Post Catching, Quality, Tuna Â Â Indonesia adalah salah satu eksportir tuna terkemuka di dunia. Total volume ekspor ikan tuna pada tahun 2004 adalah 94.221 ton senilai US 243.937 juta Namun, ekspor tuna segar telah terhambat oleh beberapa masalah kualitas, khususnya yang tinggi kandungan histamin dan logam berat. FDA (Food and Drug Administration) melaporkan bahwa selama periode tahun 2001-2005, ada 350 kasus penolakan tuna di AS karena masalah tersebut di atas. Demikian juga, dalam beberapa tahun terakhir, ekspor tuna dari Indonesia ke negara-negara anggota Uni Eropa telah mengalami RASFF (Rapid Alert System for Food and Feed) dan suspensi ekspor oleh Komisi Eropa. Jelas karena itu, bahwa upaya untuk meningkatkan penanganan pasca panen sangat penting. Penelitian ini dilaksanakan di Pelabuhan Ratu, Jawa Barat dan Pusat Penelitian Kelautan dan Perikanan Untuk Pengolahan Produk dan Bioteknologi, Jakarta. Baru menangkap ikan tuna yang dibongkar dan diangkut ke Jakarta dengan icing yang tepat. Kualitas perubahan dimonitor, termasuk suhu inti dari ikan, pH, K-nilai (inosine, hipoxantine, IMP, AMP, ADP, ATP), histamin, logam berat (Hg dan Cd), dan mikrobiologi. Nilai pH sampel tuna segar pada saat kedatangan di laboratorium bervariasi antara 5,85-6,01. Sedangkan nilai-K dan isi histamin adalah 2,01-13,74% dan 1,28-1,61 mg/100g masing. menghitung mikroba bakteri penghasil histamin adalah Total dan 102-2,5 x 104 cfu / g dan 101-1,99 x 102 cfu / g masing-masing. Mercury dan konten cadmium adalah 0,076-0,501 ppb dan 0,052-0,398 ppb masing. Kata kunci: Kualitas, Pos Penangkapan, Tuna